Influence of Temperature and Salt on Viscosity Property of Guar Gum - Srichamroen, Anchalee (Asian Health, Science and Technology Reports, 2007)
The viscosity of guar gum is one of the factors that may reduce nutrient (i.e. glucose, lipid) absorption in the intestinal lumen. Some studies have shown that viscous guar gum did not decrease nutrient absorption. Those studies, however, did not report the effect of temperature or Krebs solution on viscosity of guar gum used. Therefore, the present study determined the viscosity behavior of guar gum at different temperatures (4 oC, 25 oC, 37 oC) and different solvents (water vs Krebs bicarbonate). When the 0.5% (w/w) guar gum was heated from either 4 oC or 25 oC to physiological temperature (37 oC) and held for 2 h, the viscosity measured at 37 oC of both solutions was similar. This result was similarly observed with 1% (w/w) guar gum. Krebs bicarbonate decreased the viscosity of 0.25% (w/w) guar gum at 37 oC, but it increased the viscosity of 0.5% (w/w) guar gum at 37 oC. The results of this study may help to better understand the viscosity behavior of guar gum under processing and physiological conditions.